Comparative estimation of grain productivity and green mass of leguminous crops in the southern forest-steppe of the Republic of Bashkortostan - I. R. Yuldybaev; F. A. Davletov; K. P. Gainullina (Зерновое хозяйство России, 2024)
Leguminous crops play an important role in providing the population with high-protein products and farm animals with feed. The correct selection and distribution of species and varieties of these crops in accordance with soil and climatic conditions have a significant impact on their productivity.   The purpose of the current work was to estimate productivity of green mass, hay, grain, as well as the degree of development of traits that affect the productivity formation of peas, chickpeas, lentils, spring vetch, and fodder beans when grown in the southern forest-steppe of the Republic of Bashkortostan.   The study was carried out in 2021–2023. Contrasting weather conditions made it possible to comprehensively estimate the material being studied. The objects of the study were the varieties of five types of leguminous crops ‘Pamyati Popova’ (peas), ‘Sokol’ (chickpeas), ‘Nevesta’ (lentils), ‘Uzunovskaya 8’ (spring vetch), ‘Kalor’ (fodder beans). The trials were carried out in accordance with the Methodology of State Variety Testing (2019). As a result of the research, there were identified leguminous crops that were the most adaptive in a number of parameters for cultivation in the Southern Urals of the Republic of Bashkortostan, namely peas, chickpeas, lentils with 65.7 ± 9.7–70.7 ± 9.4 days of a vegetation period; peas with a maximum growth rate before the budding phase; peas, chickpeas, spring vetch, fodder beans with the most developed root system; peas and spring vetch with the largest number (223.3±13.3 – 236.0±17.1 pieces, respectively) and weight (0.39±0.04 – 0.45±0.07 g, respectively) of nodules per 10 plants. The maximum productivity of green mass (7.41–7.47 t/ha) and hay (1.87–1.89 t/ha) was obtained from peas and spring vetch. The maximum productivity of seeds (1.48–1.51 t/ha) was from peas and chickpeas. Thus, there has been recommended to expand pea crops, including chickpeas and lentils in the crop rotation, and restoring spring vetch crops. To achieve consistently high yields of these leguminous crops, it is necessary to sow them in the early stages with seeds of higher reproductions, treated before sowing with appropriate disinfectants and microfertilizers.